The treatment of a large acoustic tumor with fractionated stereotactic radiotherapy - McClelland, Shearwood (J Robot Surg, 2007)
The treatment of acoustic neuromas (AN) usually involves surgical excision or stereotactic radiosurgery. However, for large AN (mean diameter > 3 cm), stereotactic radiosurgery is rarely used, leaving patients with limited noninvasive treatment options. Recently, the use of fractionated stereotactic radiotherapy (FSRT) has been effective in treating small to medium-sized AN. We present a patient with a large AN treated with FSRT. The patient was a 43-year-old man presenting with imbalance, tinnitus, vertigo, and right-sided hearing decline associated with vomiting and hydrocephalus. Magnetic resonance (MR) imaging revealed a large, 3.8-cm, right cerebellopontine-angle tumor compressing the fourth ventricle. Following right frontal ventriculoperitoneal shunt placement, the patient underwent FSRT for treatment of the tumor. Using the Radionics X-Knife 4.0 3D treatment planning system, a total of 54 Gy was delivered in 1.8-Gy daily fractions with the prescription isodose line of 90%. Treatments were delivered using a dedicated Varian 6/100 linear accelerator, and head immobilization was achieved with the Gill-Thomas-Cosman relocatable stereotactic frame. The patient was subsequently evaluated with serial contrast-enhanced MR imaging. Following FSRT, local control (defined as the absence of tumor progression) was achieved, and treatment was well tolerated. There was no hearing-related, trigeminal, or facial-nerve morbidity following FSRT at 63-month follow-up. Treating a patient with a large AN with FSRT resulted in local tumor control, with no trigeminal nerve, facial nerve, or hearing-related morbidity. These results support FSRT as a potential noninvasive treatment modality for AN some would consider too large for single-fraction stereotactic radiosurgery (SRS).